TINJAUAN YURIDIS PEMUNGUTAN PAJAK HOTEL DAN HIBURAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Faharudin, Faharudin; Wulandari, Sri (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2024)
The purpose of this study is to determine the juridical review of Hotel and Entertainment tax collection based on Law number 28 of 2009 concerning local tax collection and local retribution of Baubau city, and to find out the obstacles experienced in collecting Hotel and Entertainment tax based on Law number 28 of 2009 concerning local tax collection and local retribution of Baubau city. Researchers used mixed methods, namely quantitative and qualitative. This type of research is normative juridical research using a statutory approach and conceptual approach. Data collection techniques in this research are literature study and field study. The results showed that: (1) the collection of Hotel and Entertainment tax based on Law number 28 of 2009 concerning the collection of local taxes and levies in Baubau city has been well realized; (2) in the Collection of Hotel Tax and Entertainment Tax in Baubau City there are still many obstacles faced. One of them is due to the lack of a tax collection coordinator which slows down the tax collection process.